The Effect of Mechanical Stretch on Myotube Growth Suppression by Colon-26 Tumor-Derived Factors - Halle, Jessica L.; Counts-Franch, Brittany R.; Prince, Rose M.; Carson, James A. (Frontiers in Cell and Developmental Biology, 2021)
Preclinical models and in vitro experiments have provided valuable insight into the regulation of cancer-induced muscle wasting. Colon-26 (C26) tumor cells induce cachexia in mice, and conditioned media from these cells promotes myotube atrophy and catabolic signaling. While mechanical stimuli can prevent some effects of tumor-derived factors on myotubes, the impact of mechanical signaling on tumor-derived factor regulation of myosin heavy chain (MyHC) expression is not well understood. Therefore, we examined the effects of stretch-induced mechanical signaling on C2C12 myotube growth and MyHC expression after C26 conditioned media (CM) exposure. C26 CM was administered to myotubes on day 5 of differentiation for 48 h. During the last 4 h or 24 h of C26 CM exposure, 5% static uniaxial stretch was administered. C26 CM suppressed myotube growth and MyHC protein and mRNA expression. Stretch for 24 h increased myotube size and prevented the C26 CM suppression of MyHC-Fast protein expression. Stretch did not change suppressed MyHC mRNA expression. Stretch for 24 h reduced Atrogin-1/MAFbx and MuRF-1 protein expression and increased the myogenin to MyoD protein ratio. Stretch in the last 4 h of CM increased ERK1/2 phosphorylation but did not alter the CM induction of STAT3 or p38 phosphorylation. These results provide evidence that in myotubes pre-incubated with CM, the induction of mechanical signaling can still provide a growth stimulus and serve to preserve MyHC-Fast protein expression independent of changes in mRNA expression.